2018
DOI: 10.3390/cli6030070
|View full text |Cite
|
Sign up to set email alerts
|

Urban Cold and Heat Island in the City of Bragança (Portugal)

Abstract: The thermal environment is an important aspect of the urban environment because it affects the quality of life of urban residents and the energy use in buildings. Urban Heat Island (UHI) and Urban Cold Island (UCI) are complementary effects that are the consequence of cities’ structures interference with the local climate. This article presents results from five years of urban climate monitoring (2012–2016) in a small Portuguese city (Bragança) using a dense meteorological network of 23 locations covering a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 60 publications
1
20
1
Order By: Relevance
“…The spatial resolution of Landsat-8 (30 m) was high enough to distinguish between the temperature of sites separated by only a few hundred meters and characterized by different types of land use and land cover (LULC) (e.g., green spaces and parking lots). Similar to [95], we found that green spaces were characterized by lower LST compared to paved built surfaces and bare land (the difference between the maximum and minimum LST across the 100 measurement sites was 5.5 • C). This trend was indicated by a high and significant correlation between LST and two spectral indices representing green vegetation (NDVI) and built-up land cover (NDBI) (r = −0.45 and r = 0.6, respectively, p < 0.001 for both).…”
Section: Discussionsupporting
confidence: 78%
“…The spatial resolution of Landsat-8 (30 m) was high enough to distinguish between the temperature of sites separated by only a few hundred meters and characterized by different types of land use and land cover (LULC) (e.g., green spaces and parking lots). Similar to [95], we found that green spaces were characterized by lower LST compared to paved built surfaces and bare land (the difference between the maximum and minimum LST across the 100 measurement sites was 5.5 • C). This trend was indicated by a high and significant correlation between LST and two spectral indices representing green vegetation (NDVI) and built-up land cover (NDBI) (r = −0.45 and r = 0.6, respectively, p < 0.001 for both).…”
Section: Discussionsupporting
confidence: 78%
“…In this sense, the establishment of green spaces may provide an additional role in cities creating urban cooling island (UCI) effects in pocketed regions of cities [ 63 , 64 ]. Buildings themselves can produce UCI effects during certain times of day i.e., mornings; however, green spaces can absorb additional heat during warmer times of the day and year depending on how impervious and vegetation dense such spaces are [ 64 , 65 ].…”
Section: Landscape Featuresmentioning
confidence: 99%
“…Nowadays, a large air temperature network with sufficient weather stations has overcome the limitations of spatial resolution. For example, a dense meteorological network of 23 locations across 5 y were used to monitor the urban climate in a small Portuguese city and adequate results were obtained [29]. With the advantages of high temporal resolution and accuracy, meteorological observations can provide fine-scale temporal information on UHI.…”
Section: Introductionmentioning
confidence: 99%